MALIGNANT STRUMA OVARII IN PREGNANCY - Ho, Jin Hui; Nagaratnam, Shamharini A/P (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Struma ovarii is monodermal teratoma predominantly composed of mature thyroid tissue. Thyroid tissue must comprise more than 50% of the overall tissue to be classified as a struma ovarii and it accounts for approximately 2.7-5% of all ovarian teratomas. Depending on the histological features, struma ovarii can be classified as benign or malignant. CASE We report a case of a 28-year-old primigravida Malay female. She visited the antenatal clinic on her 9th gestational week. Ultrasound of the pelvic incidentally found a right ovarian cyst measuring 9 x 8 cm located above the uterus, which is multiloculated with solid-cystic component. Otherwise, she was asymptomatic at presentation. Patient underwent laparoscopic right ovarian cystectomy on her 13th gestational week. Histopathology examination revealed a mature cystic teratoma, with papillary thyroid carcinoma arising in the background of struma ovarii. She had subclinical hyperthyroidism at early pregnancy, however normalized at her 23rd gestational week. Subsequent thyroid ultrasound was normal. She successfully delivered a healthy baby at her 38th gestational week. There was no evidence of metastasis based on the computed tomography (CT) scan of the thorax, abdomen, and pelvis. Six weeks after delivery, she underwent laparoscopic right salpingo-oophorectomy with omentectomy and right pelvic lymph node sampling which also showed no evidence of metastasis. CONCLUSION Struma ovarii is a rare ovarian tumour. A high index of clinical suspicion along with thorough clinical examination is crucial to diagnose such a tumour. Although benign forms are more common, malignant struma ovarii, mainly papillary thyroid carcinoma have also been reported. Long-term follow up is needed to detect recurrence.